2019
DOI: 10.48550/arxiv.1907.04473
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

CMB-S4 Science Case, Reference Design, and Project Plan

Abstract: This document on the CMB-S4 Science Case, Reference Design, and Project Plan is the product of a global community of scientists who are united in support of advancing CMB-S4 to cross key thresholds in our understanding of the fundamental nature of space and time and the evolution of the Universe. CMB-S4 is planned to be a joint National Science Foundation (NSF) and Department of Energy (DOE) project, with the construction phase to be funded as an NSF Major Research Equipment and Facilities Construction (MREFC)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
559
1
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

5
4

Authors

Journals

citations
Cited by 337 publications
(593 citation statements)
references
References 527 publications
(724 reference statements)
6
559
1
4
Order By: Relevance
“…This approximation inevitably induces errors when making predictions for observables because the axion field is initially effectively frozen and the approximate equations of state used to evolve the effective fluid efficiently may then be insufficiently accurate. Even for axions in the range 10 −27 eV m 10 −24 eV where the clustering suppression in linear theory is testable with CMB measurements and the timescale hierarchy is less extreme, these errors already been shown to be significant at the 1 ∼ 2σ level [24] for upcoming experiments like CMB-S4 [25]. Other similar averaging approches such as the one proposed by Ref.…”
Section: Introductionmentioning
confidence: 74%
“…This approximation inevitably induces errors when making predictions for observables because the axion field is initially effectively frozen and the approximate equations of state used to evolve the effective fluid efficiently may then be insufficiently accurate. Even for axions in the range 10 −27 eV m 10 −24 eV where the clustering suppression in linear theory is testable with CMB measurements and the timescale hierarchy is less extreme, these errors already been shown to be significant at the 1 ∼ 2σ level [24] for upcoming experiments like CMB-S4 [25]. Other similar averaging approches such as the one proposed by Ref.…”
Section: Introductionmentioning
confidence: 74%
“…For a halo mass threshold of M min = 2×10 11 M and θ f = 1 arcmin, we find the total S/Nf −1/2 sky ≈ 15 and 10 for C τ g and C τ y , respectively. After delensing the lensed B-mode power spectrum at level of 90% (Smith et al 2012;Abazajian et al 2019), we find that the signal-to-noise ratio increases by 14% and 12.5% for C τ g and C τ y , respectively.…”
Section: Detectability Of Signalsmentioning
confidence: 92%
“…We calculate the τ reconstruction noise for CMB S4 like experiments with 1µK arcmin sensitivity in temperature and 1 arcmin beam size (Abazajian et al 2019). Unless mentioned, we use l min = 30 and l max = 5000 throught this work because a CMB-S4-like experiment will make observations at these scales.…”
Section: τ Reconstruction Noisementioning
confidence: 99%
“…We then smooth the maps by 90 , representative of the resolutions of current and near future SZ surveys with e.g. Advanced ACTpol, Simons Observatory, and CMB-S4 (see Henderson et al 2016;Abazajian et al 2019;Ade et al 2019), and by 10 , representative of larger single dish facilities such as At-LAST, the Green Bank Telescope, the Sardinia Radio Telescope, and the Large Millimeter Telescope (see respectively Klaassen et al 2020;Dicker et al 2014;Hughes et al 2020), as shown in Figures 17 and 18 respectively. For both resolutions, we choose representative redshifts of z = 0.057, z = 0.3, and z = 0.87, corresponding approximately to the redshifts of the famous massive merging systems A3667, the Bullet cluster, and El Gordo.…”
Section: Insights From the Kinetic Sunyaev-zeldovich Effectmentioning
confidence: 99%